COMPLICATED MIGRAINE - Kadek Putri Paramita Abyuda; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2021)
Migraine is a chronic paroxysmal neurological disease characterized by attacks of moderate or severe headache accompanied by reversible neurologic and systemic symptoms. Although not life threatening, migraine can cause disability in the productive population. Migraine sufferers generally have a family history of migraine so that migraine is considered a genetic disease. Endogenous psychological factors such as stress or fatigue are the main triggers for migraine. Migraine pathophysiology involves various parts of the brain so that migraine symptoms are complex. Management of acute migraine can be done pharmacologically and non-pharmacologically. Migraine preventive management is needed if the patient has a chronic migraine or does not respond to abortive treatment.